2005
DOI: 10.1007/s10763-005-9014-7
|View full text |Cite
|
Sign up to set email alerts
|

Student Views of Concept Mapping Use in Introductory Tertiary Biology Classes

Abstract: ABSTRACT. Introductory tertiary level science classes (i.e., at the university or postcompulsory school level) including those for biology face increasing diversity in intake. Previous research has indicated university level teachers assume a certain level of prior knowledge which may or may not be possessed by such students. This report focuses on the use of concept mapping in introductory biology tutorial classes. The research findings suggest that the students found the use of concept mapping enjoyable and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 39 publications
2
28
0
Order By: Relevance
“…In addition, by means of a survey, the studentsí opinions on the experience have been gathered to improve the design of the experience (Buntting et al, 2006;Murga-Menoyo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, by means of a survey, the studentsí opinions on the experience have been gathered to improve the design of the experience (Buntting et al, 2006;Murga-Menoyo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This graphic representation of concepts provides students and teachers a suitable tool to organise, summarise and communicate their knowledge about any topic, showing information in a schematic and organised way. Consequently, students can use concept mapping as a learning strategy for any subject since it promotes individual or collaborative, reflexive and meaningful learning (Buntting et al, 2006). Additionally, teachers can use concept mapping as teaching resources to show the structure of a topic or to analyse the relationships among the concepts related to the topic (Novak & Cañas, 2006).…”
Section: Concept Mapping and Information Technologies Tools In Teachementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, within the content-heavy context of biology, first-year students would require support for their engagement with their notes. Lecturers in biology usually use multiple representations when explaining content in class; these representations are meant to support learning (Buntting, Coll, & Campbell, 2006). Findings showed that lecturers' slides varied in the quantity and type of detail that was presented during lectures; slides provided by some lecturers comprised wordy content whilst slides presented by other lecturers contained mostly key points or key words (Table 3).…”
Section: Students' and Lecturers' Use Of Lecture Slides In The First mentioning
confidence: 99%
“…Thus, while note-taking is mechanistic, during the process of note-making students could engage more readily in deepening their understanding of content (Makany, Kemp, & Dror,Research on compiling notes in science emphasises the role of multi-representation (e.g. formulae; textual explanations; diagrams) and explores the opportunities for concept mapping and sketches (Buntting, Coll, & Campbell, 2006). The context of this study includes note-making strategies that students use when composing their study notes, and is based on the multiple representations which the lecturer presents during class.…”
Section: Introductionmentioning
confidence: 99%